Boosting efficacy of nurse-led stop smoking interventions with a quit and win contest: pilot study results. Issue 4 (4th July 2018) - Wong, Grace; Glover, Marewa; McPherson, Mervyl; Garrett, Nick; McLeod, Shona
Abstract : Background: Grave disparities in smoking prevalence exist between indigenous Māori, Pacific Island peoples, and other New Zealanders. Primary care nurses routinely provide brief stop smoking interventions to achieve national targets but they are constrained by time. Innovations using new technologies offer opportunities to enhance brief interventions and improve uptake and outcomes. Objectives/Aims/Hypotheses: This study explored the feasibility of adding a novel scratch card and internet-based, quit and win contest with mobile phone support messages, to practice nurses' brief smoking cessation interventions. Design: Pragmatic exploratory mixed methods pilot study comprising a quantitative two-group comparison and qualitative interviews. Methods: In two intervention clinics, practice nurses added supportive mobile phone messages, novelty scratch cards to win online prizes and 1000 prize draw entry following 1 month smokefree, to routine brief stop smoking interventions. In three control clinics, patients who smoked received brief stop smoking interventions only. Practice nurses collected baseline and 1-month data describing patients' smoking status, quit attempts, and cessation support. Researchers conducted qualitative interviews with two nurses and ten patients and collected 3-month data. Results: Five primary care clinics recruited 67 smokers (37 intervention; 30 control). The contest was readily incorporated into nurses' practice. It appealed to nurses and Māori and Pacific Island patients, increased time to first cigarette, and attracted first time quitters. However, it had no extra effect on smoking cessation compared with usual care. Pacific Island patients' participation in the online elements was limited by low access to the internet. Conclusions: While the exploratory study did not indicate the potential for triggering mass quitting, reduced dependency was suggested. The intervention attracted Māori and Pacific Island smokers and engaged first time quitters. Low cost, novelty activities could be used to refresh routine brief stop smoking interventions, and to motivate practice nurses to engage more smokers in quitting.